2016
DOI: 10.1016/j.joep.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Locus of Control and low-wage mobility

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 50 publications
0
16
0
4
Order By: Relevance
“…However, the timing of measurements is also an advantage with regard to causality, as we show that income from the previous year predicts current sense of control and life satisfaction, as well as subsequent mental health. In combination with the robust effects of within-person changes, it thus seems likely that economic vulnerability undermines sense of control and in turn mental well-being, rather than (or in addition to) trait sense of control predicting earnings (see Schnitzlein & Stephani, 2016;Spears, 2011). Future studies could theorize more explicitly on temporal aspects in the relationship between economic vulnerability and mental well-being, such as adaptation to chronic versus occasional economic vulnerability, as it has been discussed for other economic stressors (e.g.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…However, the timing of measurements is also an advantage with regard to causality, as we show that income from the previous year predicts current sense of control and life satisfaction, as well as subsequent mental health. In combination with the robust effects of within-person changes, it thus seems likely that economic vulnerability undermines sense of control and in turn mental well-being, rather than (or in addition to) trait sense of control predicting earnings (see Schnitzlein & Stephani, 2016;Spears, 2011). Future studies could theorize more explicitly on temporal aspects in the relationship between economic vulnerability and mental well-being, such as adaptation to chronic versus occasional economic vulnerability, as it has been discussed for other economic stressors (e.g.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Additionally, as stated by Heckman (2011, p. 31), policy makers would gain a new 'avenue for intervention and policy' as the psychological impact of unemployment has been underestimated so far. Gathering specific insights on LOC's stability after job-loss, during unemployment 1 Additionally, studies have found an significant effect of LOC on entrepreneurial activity (Hansemark, 2003;Caliendo et al, 2014), occupational attainment and advancement (Andrisani, 1977;Cobb-Clark and Tan, 2011;Ahn, 2015;Schnitzlein and Stephani, 2016), maternity leave (Berger and Haywood, 2016), internal migration (Caliendo et al, 2015a), health behavior (Cobb-Clark et al, 2014), parental investment (Lekfuangfu et al, 2017), unemployment duration (Uhlendorff, 2004), selection into performance appraisal (Heywood et al, 2017), job satisfaction (Ng et al, 2006) and employment-related training (Caliendo et al, 2016). See Cobb-Clark (2015) for a comprehensive overview on LOC and labor market outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Further measures of personality traits are an individual's Locus of Control (LoC) and an individual's reciprocity. LoC is associated with an individual's perception that his or her outcomes in life are mainly affected by the actions of other people and are thus beyond their control (see, e.g., Rotter, ; Schnitzlein and Stephani, ). Reciprocity refers to the individual's behaviour with respect to friendly/unfriendly actions of other people.…”
Section: Economic Backgroundmentioning
confidence: 99%
“…A high value of a trait constructed in this way indicates a high outcome of the respective personality dimension (see Heineck and Anger, ). For the construction of LoC, we rely on a procedure suggested by Schnitzlein and Stephani (), which is more general than the concept used by Heineck and Anger (). Seven items with responses on a 7‐point Likert scale are used.…”
Section: Data and Economic Approachmentioning
confidence: 99%